A transcultural approach: mapping cosmopolitanism in Zadie Smith’s White Teeth (2000) (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2023)
This paper aims to probe into the transcultural aspect of White Teeth by Zadie Smith. Under transculturalism, cosmopolitanism is pivotal in transcending ethnographic and cultural borders. Zadie Smith’s avant-garde effort to acknowledge people around the globe about the perks of a communal society is phenomenal. Her novel addresses thematic concerns of immigration, postcolonial conflicts, globalization, multiculturalism, and identity. Previously, her novel was read and discussed as a postcolonial text. However, this research paves the way to re-read it through a liberal lens and delineates the cosmopolitan approach proposed by Kwame Anthony Appiah. The novel invites readers to consider the complexities of living in a world where cultures intersect, clash, and coexist. This article explains the relationship between the main characters in addition to the bildungsroman of the second generation. The generational differences within families highlight the evolving nature of cosmopolitanism as the characters attempt to reconcile their heritage with their present circumstances. Zadie Smith’s technique of inter-narrativity rekindles hope in global citizens to build a transcultural society together. The article directs the audience to see beyond the postcolonial intrusions and accept intercultural changes as challenges needed to move and grow in this era of globalization.